POSSIBLE GENERATION OF HYDROGENIC GOLD DEPOSITS - Tauson L.V.; Lomonosov I.S.; Glyuk D.S.; Zagoskin V.A.; Koroleva G.P. (My University, 1989)
Recent investigations have shown that gold has a relatively high migration ability in the supergene zone. Under exogene conditions it is very mobile in both acid and alkaline media and not only can become dispersed, but can also be concentrated at geochemical barriers. The present authors' investigation of the forms of migration and the conditions of secondary concentration of gold in the supergene zone by physicochemical modeling indicated that native gold could be produced by disproportionation as a result of alteration of the physicochemical conditions. Thus, under favorable conditions in the supergene zone, native gold many separate from aqueous solutions and undergo secondary concentration. In essence, this is the basis of the principle of development of zones of secondary enrichment of gold in the weathered mantles of many gold ore deposits, and especially in gold-sulfide deposits with finely divided gold.